Dried tea residue can alter the blood metabolism and the composition and functionality of the intestinal microbiota in Hu sheep - Guo, Liangyong; Yu, Shiqiang; Cao, Fang; Zheng, Kaizhi; Li, Manman; Peng, Zhenying; Shi, Xingyun; Liu, Liping (Frontiers in Microbiology, 2023)
Ruminant animals face multiple challenges during the rearing process, including immune disorders and oxidative stress. Green tea by-products have gained widespread attention for their significant immunomodulatory and antioxidant effects, leading to their application in livestock production. In this study, we investigated the effects of Dried Tea Residue (DTR) as a feed additive on the growth performance, blood biochemical indicators, and hindgut microbial structure and function of Hu sheep. Sixteen Hu sheep were randomly divided into two groups and fed with 0 and 100g/d of DTR, respectively. Data were recorded over a 56-day feeding period. Compared to the control group, there were no significant changes in the production performance of Hu sheep fed with DTR. However, the sheep fed with DTR showed a significant increase in IgA (P＜0.001), IgG (P=0.005), IgM (P=0.003), T-SOD (P=0.013), GSH-Px (P=0.005), and CAT (P＜0.001) in the blood, along with a significant decrease in albumin (P=0.019), high density lipoprotein (P=0.050), and triglyceride (P=0.021). DTR supplementation enhanced the fiber digestion ability of hindgut microbiota, optimized the microbial community structure, and increased the abundance of carbohydrate-digesting enzymes. Therefore, DTR can be used as a natural feed additive in ruminant animal production to enhance their immune and antioxidant capabilities, thereby improving the health status of ruminant animals.